Pembelajaran Pemberian Reward Terhadap Kemampuan Menulis Teks Prosedur Siswa Kelas VII MTs - Badi’us Syayyidah; Sukiman Sukiman; Tsalitsatul Maulidah (FKIP, Universitas Billfath Lamongan, 2022)
This research aims to determine the effect ofgiving rewards on the ability to write procedural texts in Indonesian subject. This researrch includes quantitative research, this research is focused on giving rewards related to the ability to write procedural texts, the research datawas take in may 2021. The research data was abtained using one pre-experimental class, this study was in the from of one grub pretest, the average score was 58.89, the posstest abtained on average score of 85.56. Besed on using the reward method, this research shows that the differences in the results of students’ learning abilities before being given trearment and already being give treatment can be seen from the results of pretest and posstest. From the research data, it can be concluded that the pretest anda posstest scores are different.